Investing in a Foreign Startup Company: Luckin Coffee Inc. - Lin, YingChou; Richards, Rhonda; Xu, Hanzhi (Journal of Accounting and Finance, 2024)
Many foreign companies, particularly from emerging markets, have been listed on the US stock markets as a form of American depositary receipt or share (ADRs or ADS) in recent years. Although those US-listed foreign stocks provide a great opportunity for domestic investors to diversify their portfolios, they could also add additional risks to investors unfamiliar with those companies’ business strategies, corporate governance, investor protection, and accounting or audit practices in their home countries. In this case, we introduce Luckin Coffee Inc., a Chinese startup coffeehouse chain that went public on the Nasdaq in 2019. This case aims to guide students in evaluating a foreign startup company’s investment by examining its business strategies, operating performance, corporate governance, and auditing practices when limited company history and financial data are available. It also allows students to research companies’ filings to identify useful information for investment decisions.